A disputa jurisdicional do management como profissão no contexto brasileiro: uma reflexão da participação do sistema CFA/CRAS - Cicmanec, Édna Regina (2014)
This study aims to assess the participation of the national representative association of Management (consisting of twenty-six regional councils of administration in each Brazilian state including the Federal District entitled CFA /CRAs system), on jurisdictional dispute of the profession in Brazil. The analysis sets a starting review on theoretical basis supported by the sociological approach of professions, which nowadays presents the best database to the referred assessment on the professional phenomenon, complemented by studies in the field of administration. These studies are conspicuous by their reconstruction of elements described in the constitution, the development of Management attributions and consequent recognition as a profession. The research sought to assess the way actions developed by the CFA /CRAs system contributed to the jurisdictional dispute of the occupation in the country. In the approach proposed by Abbott (1988), the jurisdictional dispute corresponds to professional and competitive intelligence in the job market among occupations that aim to exercise the exclusive domain over the same set of activities. The study that contemplates a historical qualitative approach of exploratory descriptive nature with a longitudinal cut was developed from two separate axes. The first had as main objective the historical recovery of three further categories, which together provide a broader assessment of the phenomenon: socio-historical context; Statute of Management and National Representative Association. The second has excelled in the evaluation of the actions promoted by the CFA/CRAs system which support the profession intermingling three other analytical categories: Knowledge system, Social Structure and Professional Boundaries, which, according to Abbott (1988) are directly responsible for the maintenance of the acting space (jurisdiction) of a profession. The primary and secondary database used in the investigation was composed of a vast amount of physical and digital documents (laws, regulations, resolutions, newsletters, manuals, codes of ethics, magazines, publications, reports among others) complemented by personal interviews, questionnaires and statements online, in addition to the bibliography used in the composition of the additional categories. The method of evaluation used in Historical Research with a focus on Traditional Historiography and the Technique of Content Analysis of Bardin (1977) were employed for treatment and analysis of the data. As main results, the research concluded that the set of actions undertaken by the CFA/CRAs system for the profession of Management in Brazil has contributed positively to the activity. However, these actions appeared to be still inadequate when assigned in greater legitimacy to the knowledge system of the profession, a better social structuring of its members and a more effective protection of their professional limits. Non-compliance may in part be linked to the occurrence of other factors, that when analyzed together with focus directly on the allocation of a greater cultural legitimacy to the occupation affects its ability to defend itself from other interested professions who invest on their jurisdictional space, consequently determining its status in the Brazilian professional system.